2001
DOI: 10.1590/s0073-47212001000100018
|View full text |Cite
|
Sign up to set email alerts
|

Influência do ciclo lunar na captura de Aedes scapularis (Diptera, Culicidae) na Mata Atlântica do Paraná

Abstract: scapularis (Rondani, 1948) was studied in a small area of the Atlantic Forest, Serra do Marumbi, Morretes, Paraná, Brazil. Adults were captured with Shannon light traps for 48 nights, representing 12 nights for seven time intervals. Traps were operated from dusk to dawn. The influences on flight activity of the lunar phase, ambient temperature, relative humidity, and rainfall were analyzed. Ae. scapularis had a flight behaviour different in each of the four lunar phases. In relation to flight period, the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Sant'Ana & Lozovei 2001;Silva et al 2004;Bona & Navarro-Silva 2008). In the western region of the state, forests have been reduced to small fragments near rivers and creeks because of the land use mainly for agriculture.…”
mentioning
confidence: 99%
“…Sant'Ana & Lozovei 2001;Silva et al 2004;Bona & Navarro-Silva 2008). In the western region of the state, forests have been reduced to small fragments near rivers and creeks because of the land use mainly for agriculture.…”
mentioning
confidence: 99%
“…The problem might be exacerbated if the relative abundance of biting vectors also increased at this time. Although many studies have found this to be the case (Bidlingmayer, 1964; Pandian & Chadrashekan, 1980; Charlwood et al , 1986a; Birley & Charlwood, 1989; Chadee, 1992), others have failed to demonstrate any effect of moonlight on mosquito densities (Singh et al , 1996) and yet others have described lower densities at full moon periods (Miller et al , 1970; Davies, 1975; Rubio‐Palis, 1992; Constantini et al , 1998; Sant’Ana & Lozovei, 2001; Souza et al , 2005). Some of these authors used light traps to collect mosquitoes outside.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the samples in the collection are from the dense ombrophilous forest phytogeographic region ( n = 4,831), with 4,774 (98%) of these being from the municipality of Morretes. Bearing in mind the availability of conservation areas in the region, Morretes has long been used by different researchers as a place for culicid collection [ 87 90 ] . …”
Section: Methodsmentioning
confidence: 99%
“…These data were the basis for creating a map covering the phytogeographic areas [ 85 ] , utilizing QGIS software (V. 3.22.3-Białowieża, RRID: SCR_018507 ) [ 92 ] . The culicids in the collection were captured by different methods, such as entomological nets, aspiration, US Centers for Disease Control (CDC) light traps, and Shannon traps containing a fluorescent bulb as bait [ 13 , 87 , 88 ] . …”
Section: Methodsmentioning
confidence: 99%